Rediscovery of Leptochilus hemionitideus (C.Presl) Noot. (Polypodiaceeae): first collection in 140 years from the Western Ghats of Karnatak - Bagathsingh; Benniamin, A (BRIN Publishing (Penerbit BRIN), 2025)
BAGATHSINGH, C. & BENNIAMIN, A. 2025. Rediscovery of Leptochilus hemionitideus (C.Presl) Noot.(Polypodiaceeae): first collection in 140 years from the Western Ghats of Karnataka. Reinwardtia 24(1): 27‒31. —This study presents the recollection of Leptochilus hemionitideus (C.Presl.) Noot. (Polypodiaceae), a species presumed to have an extremely small population, which has not been observed since the collections made by R.H. Beddome (1883) in the Western Ghats of Karnataka. The paper provides detailed notes on its taxonomic uncertainty, aprecise description, and photographs of its micromorphology to aid in its identification.